2016
DOI: 10.1021/acs.jmedchem.5b01203
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Monocarbonyl Ligustrazine–Curcumin Hybrids for Intervention of Drug-Sensitive and Drug-Resistant Lung Cancer

Abstract: The elevation of oxidative stress preferentially in cancer cells by inhibiting thioredoxin reductase (TrxR) and/or enhancing reactive oxygen species (ROS) production has emerged as an effective strategy for selectively targeting cancer cells. In this study, we designed and synthesized 21 ligustrazine-curcumin hybrids (10a-u). Biological evaluation indicated that the most active compound 10d significantly inhibited the proliferation of drug-sensitive (A549, SPC-A-1, LTEP-G-2) and drug-resistant (A549/DDP) lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 80 publications
1
39
0
Order By: Relevance
“…All of the five compounds exerted potent TrxR inhibitory activity (IC 50 = 1.22–4.73 μM). Most surprisingly, compound 211 exhibited the highest TrxR inhibitory activity, which was ∼32‐fold more potent than positive drug curcumin . The interaction of dimethoxycurcumin ( 216 , Figure ) with TrxR was explored by Sandur and co‐workers.…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%
“…All of the five compounds exerted potent TrxR inhibitory activity (IC 50 = 1.22–4.73 μM). Most surprisingly, compound 211 exhibited the highest TrxR inhibitory activity, which was ∼32‐fold more potent than positive drug curcumin . The interaction of dimethoxycurcumin ( 216 , Figure ) with TrxR was explored by Sandur and co‐workers.…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%
“…The complex chemistry of curcumin allows it to inhibit multiple oncogenic processes, including those associated with the JAK2/STAT3 pathway or the induction of ROS production293031. To improve the potency of curcumin as a cancer therapeutic agent, many synthetic curcumin analogues have been developed as new JAK2/STAT3 inhibitors, including FLLL31, FLLL32 and FLL62171819.…”
mentioning
confidence: 99%
“…15,16 Accordingly, ligustrazine has attracted considerable attention as a privileged scaffold in cancer drug discovery. In this context, several studies reported the development of different ligustrazine-based hybrids such as ligustrazine-curcumin hybrids, 17,18 ligustrazine-terpenes hybrids 19 and others. 20,21 The aforementioned findings have inspired and guided us to design and synthesize a new set of HDAC inhibitors (7a-c and 8a,b) utilizing ligustrazine as a novel cap moiety, and achieving the pharmacophoric features required to induce the desired inhibition ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%